Effect of the cement paste volume on the consistency of mixes for high performance massive and self-compacting concretes - Zarzycki, Bartłomiej; Piasta, Wojciech (Budownictwo i Architektura / Civil and Architectural Engineering, 2015)
The article presents the results of research concerning the influence of the volume of cement paste and the w/c ratio on the consistency of concrete mixes for high-performance massive and self-compacting concrete. The research covered six types of concrete mixes containing from 220 to 420 dm3 of cement paste in a cubic meter. Three of them were designed as high-performance concrete and for comparison three conventional ones. The consistency was tested with two methods: concrete slump test and flow table test, also additional tests of self-compacting mix were made. Compressive strength test were conducted to prove that concretes are high-performance. A high influence of the volume of cement paste on the workability and consistency of fresh concrete mix has been found, while the influence of the w/c ratio is considerably lower due to the dosage of high-quality superplasticizer.